Neuropathology of Autosomal Dominant Alzheimer Disease in the National Alzheimer Coordinating Center Database. Issue 3 (17th February 2016) - Ringman, John M.; Monsell, Sarah; Ng, Denise W.; Zhou, Yan; Nguyen, Andy; Coppola, Giovanni; Van Berlo, Victoria; Mendez, Mario F.; Tung, Spencer; Weintraub, Sandra; Mesulam, Marek-Marsel; Bigio, Eileen H.; et al.
Abstract: Alzheimer disease (AD) represents a genetically heterogeneous entity. To elucidate neuropathologic features of autosomal dominant AD ([ADAD] due to PSEN1, APP, or PSEN2 mutations), we compared hallmark AD pathologic findings in 60 cases of ADAD and 120 cases of sporadic AD matched for sex, race, ethnicity, and disease duration. Greater degrees of neuritic plaque and neurofibrillary tangle formation and cerebral amyloid angiopathy (CAA) were found in ADAD (p values < 0.01). Moderate to severe CAA was more prevalent in ADAD (63.3% vs. 39.2%, p = 0.003), and persons with PSEN1 mutations beyond codon 200 had higher average Braak scores and severity and prevalence of CAA than those with mutations before codon 200. Lewy body pathology was less extensive in ADAD but was present in 27.1% of cases. We also describe a novel pathogenic PSEN1 mutation (P267A). The finding of more severe neurofibrillary pathology and CAA in ADAD, particularly in carriers of PSEN1 mutations beyond codon 200, warrants consideration when designing trials to treat or prevent ADAD. The finding of Lewy body pathology in a substantial minority of ADAD cases supports the assertion that development of Lewy bodies may be in part driven by abnormal β-amyloid protein precursor processing.